Estimating the impact of antiretroviral therapy: regional and global estimates of life-years gained among adults. (23rd November 2010) - Mahy, Mary; Stover, John; Stanecki, Karen; Stoneburner, Rand; Tassie, Jean-Michel
Abstract : Objective: An estimated 4.9 million adults received antiretroviral therapy (ART) in low and middle income countries in 2009. A further estimated 700 000 adults received ART in high-income countries. The impact of providing ART is not often quantifiable due to limited monitoring systems. One measure, life-years gained, provides a standardised measure that shows the survival impact of ART on the population while controlling for variations in underlying survival. Measuring life-years gained allows a comparison of the impact of ART between regions. Methods: Using the Spectrum computer package, two different scenarios were created for 151 countries. One scenario describes the results of providing adults with ART as reported by countries between 1995 and 2009, the second scenario describes a situation in which no ART was provided to adults living with HIV between 1995 and 2009. The difference in the number of life-years accrued among adults in the two scenarios is compared and summarised by geographical region. Results: An estimated 14.4 million life-years have been gained among adults globally between 1995 and 2009 as a result of ART. 54 % of these years were gained in western Europe and North America, where ART has been available for over 10 years. In recent years the growth in life-years has occurred more rapidly in sub-Saharan Africa and Asia. Discussion: The substantial impact of ART described here provides evidence to argue for continued support of sustainable ART programmes in low and middle-income countries. Strengthening ART monitoring systems and mortality surveillance in low and middle-income countries will make this evidence more accessible to programme managers.